A COEUR cohort study of SATB2 expression and its prognostic value in ovarian endometrioid carcinoma - Cécile Le Page; Martin Köbel; Liliane Meunier; Diane M Provencher; Anne‐Marie Mes‐Masson; Kurosh Rahimi (Wiley, 2019)
Abstract The aim of this study was to describe the expression of special AT‐rich sequence‐binding protein 2 (SATB2) in ovarian endometrioid carcinoma (EC). SATB2 is a nuclear matrix‐associated transcription factor that is associated with abnormal expression in certain cancers but has not been reported for ovarian carcinoma. SATB2 mRNA and protein expression was first assessed in a pilot cohort of 26 samples by Affymetrix microarray and by routine immunohistochemistry on a small tissue microarray. A large multicenter validation cohort representing the well‐characterized cases of 235 ovarian EC from the Canadian Ovarian Experimental Unified Resource (COEUR) was then used to validate this result and to assess the prognostic impact of SATB2 expression. SATB2 staining was scored as negative, weak, moderate, and strong intensity, and by percentage of stained cells. No SATB2 expression was observed in clear cell carcinomas but 10% (n = 3) of the ECs in the pilot cohort showed SATB2 expression. In the validation cohort, strong expression was observed in 11% of ECs, while weak or moderate expression levels were detected in 12% of cases. Evaluation of SATB2 expression with clinicopathological parameters revealed an association with patient age and Federation International of Gynecology and Obstetrics grade but not with disease stage or postoperative residual disease. Any expression of SATB2, independent of intensity, was also associated with longer survival and improved progression‐free survival with hazard ratio (HR) = 0.14 (95% CI 0.03-0.56) and HR = 0.16 (95% CI 0.02-1.24) respectively. A greater beneficial effect was observed in patients with stage III/IV disease compared to patients with stage I/II disease. Furthermore, direct comparison of SATB2 with other reported prognostic biomarkers such as progesterone receptor, CDX2 and β‐catenin within this cohort showed that SATB2 had the strongest association with survival. Given the current lack of accurate prognostic factors for these patients, SATB2 has promising clinical utility and warrants further study.